Efeitos prospectivos da inconstutucionalidade : decisão político-partidária? - Bandeira, Luciana de Assunção Macieira (2013)
The Law number 9.868/99 has significantly changed the Brazilian constitutionality control system, an important instrument for defending the maintenance of the Democratic State of Law, breaking the dogma of the nullity of unconstitutional acts and it created a modulation of the effects of unconstitutionality decisions. The research has carried out quantitative and qualitative analysis, with case studies corresponding to 1,232 merit judgment sentences issued by the Supreme Federal Court, between the years of 1988 and June 30, 2013, in the course of abstract constitutionality review. The objective was to identify if there is political party influence in the modulation of effects of the unconstitutionality decision, identifying the external and internal factors that have interfered in the studied judgments. The research has evaluated the available samples from the statistical lists of the direct claim of unconstitutionality and declaratory action in the Supreme Court´s website, which has allowed us to locate each action judged in its merit and to consult vote by vote. The research has discovered that, between 1988 to 2013, 18 (eighteen) cases had refused to modulate the effects of its own decisions, and 37 (thirty seven) sentences allowed pro futuro, ex nunc and pre-arranged date effects, corresponding to 4.5% of the cases judged on merit. The study has classified the data regarding their modulated deadline, the beneficiaries and the object of the modulations. Of the 37 (thirty seven) cases identified with modulation, the research diagnosed 13 (thirteen) with strong signs of political party influence. The votes have also shown other interference factors: internal influence by the peers at the Court, for social and economic reasons (structuring theory of law), and even on behalf of the decision coherence with other precedents (Dworkin's integrity theory). In all the thirteen judged cases, the modulation requests were made by the president or by state governor. In 7 (seven) cases, the associate justices changed theirs votes to adhere to the consensually debated modulation. In all cases there was a discussion of financial-economic factors which involved the public treasure. The study has compared the discovered values with the foreign constitutional doctrine and the jurisprudential experience from Austria, USA and Germany, which have directly or indirectly influenced the national constitutional review system. This analysis has described the similarities and differences in the composition and functionality of the Court, as well as the species, extension and effects of unconstitutionality abstract and concrete review. The hypothesis problematized in the research was proved, regarding the occurrence of political party influence, which also occurs at foreign courts whose composition is determined by the Parliament or by the Chief of the Executive branch, but this influence would not have an exclusive character in determining the modulation of effects of unconstitutionality sentences. It was concluded that, in Brazil, the choice of 8 (eight) from the 11 (eleven) ministers by a same party was determinant to make the Court suffer political party influence throughout the years. The possibility of unconstitutionality modulation interferes directly in the public policies implemented by the State and Federal government, which aggravated the political pressure suffered by the judges. Since the modulation uses undetermined concepts of juridical security and exceptional social interest, though many influences external do the positive system have been detected, social aspiration demands the fulfillment of the minimal limits foreseen in the very system for fulfilling of this "open organization of the norm" to avoid arbitrariness.